Analysis of unbraced frame using ANSYS - Lee, Ying Ying (2012)
Construction of structures using steel as the construction material has become one of the major alternatives to the conventional reinforced concrete. Frame is one of the important components for a structure and need to be analyzed in such a way that they have enough strength and rigidity to satisfy the strength and serviceability limitation. Although there are many existing commercial engineering software such as STAAD.Pro, LUSAS, MATLAB and etc, but most of them are expensive and it is hard for those small companies to get the license easily. Among the various numerical methods, finite element analysis is very popular and widely used for solving engineering problems. Finite element analyses already become an integral part of computer aided engineering. ANSYS is a general purpose finite element modeling for numerically solving wide variety of structural analysis problems which include static structural analysis for both linear and nonlinear and heat transfer. Here, the study was conducted to prove finite element analysis using nonlinear analysis is able to give a similar result as the lab test. This report presents the frame finite element analysis software using ANSYS. The objective of this study is analysis the strength behavior of unbraced frame under various loading which include the gravity and wind load. A step-by-step Finite Element formulation of unbraced frame is discussed and Graphical User Interfaces (GUis) was developed so as to provide user-friendly environments. At the end of the study, results generated from the truss analysis software are compared with the existing engineering software ST AAD.Pro. for validation.